Ko Ko Mo Resort's Green Marketing Strategy To Improve Occupational Levels - Ahmad, Ahmad; Yasa, I Putu Buda; Uli, Aprila Sinta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Based on the results of the observations above, it is known that the best achievement was in June 2023, namely reaching 91.67%, this was because it coincided with the 2023 Eid holiday and was connected with school children's holidays. While in January-May the achievement still fluctuated between 75% to 83.33%. The achievement of the occupancy rate at Kokomo Resort has not been maximized, so it is necessary to carry out further research on this matter. The author plans to use a green marketing strategy to increase the achievement of occupancy rates at Kokomo Resort. The location of this research was conducted at Kokomo Resort which is located in Gili Indah Village, Gili Trawangan, Lombok. This research was conducted for 6 months, from January 2023 to June 2023. The object of this research is a green marketing strategy to increase occupancy rates at Kokomo Resort. The population in this study were the Kokomo Resort managers and their staff, totaling 5 people. The sampling technique in this study used a total sampling technique, meaning that all members of the population were sampled. The green marketing strategy at Kokomo Resort is in the good category, with an average achievement of 84%. The most dominant indicator, namely the provision of discounted room rates according to the season and the intensity of promotions through travel agents, received the highest achievement score, which was 90%. While the lowest achievement indicator is the adjustment of room rates according to certain conditions and the ease of getting public transportation by 78%.